1986
DOI: 10.1126/science.3941902
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Translocation in Mice with a Neurological Defect

Abstract: A semisterile male translocation heterozygote [t(2; 14) 1Gso] that exhibited neurological symptoms and an inability to swim (diver) was found among the offspring of male mice treated with triethylenemelamine. All breeding and cytogenetic data showed a complete concordance between translocation heterozygosity and the neurological disorders. Homozygosity for the translocation seemed to be lethal at an early embryonic stage. Despite the distinctive neurologic symptoms, no anatomic or histological defects in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Studies of the effects of TEM on mouse germ cells have shown this chemical to be highly mutagenic, causing specific-locus mutations in both poststem cell and stem-cell spermatogonial stages (28). TEM is a primary carcinogen that has experimentally produced a variety of cancers (33,36) and was implicated in the production of an inherited reciprocal translocation that produced a neurological disease with characteristics like that of a single gene dominant trait (30). Thus, for this drug, the correlation between specific-locus mutagenicity, clastogenicity, the production of a genetic disease in mammals, cancer induction, and increase in the CVs of DNA flow histograms is well established.…”
mentioning
confidence: 99%
“…Studies of the effects of TEM on mouse germ cells have shown this chemical to be highly mutagenic, causing specific-locus mutations in both poststem cell and stem-cell spermatogonial stages (28). TEM is a primary carcinogen that has experimentally produced a variety of cancers (33,36) and was implicated in the production of an inherited reciprocal translocation that produced a neurological disease with characteristics like that of a single gene dominant trait (30). Thus, for this drug, the correlation between specific-locus mutagenicity, clastogenicity, the production of a genetic disease in mammals, cancer induction, and increase in the CVs of DNA flow histograms is well established.…”
mentioning
confidence: 99%
“…Admittedly, the natures of most of these mutations remain unclear. However, at least two dominant mutations have been associated with deletions [ThP, Brachyury-hairpin (36); W19H, Dominant spotting-19H (37)] and others have been associated with translocation breakpoints [ five Si (Steel) mutations (38, and L. B. Russell, unpublished observations) and the "Diver" neurological mutation (39)], much the same as a dominant phenotype of oncogenesis is often associated with translocations in somatic cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, heritable translocations induced by chemical mutagens are sometimes associated with neurological disorders, blindness, and skeletal abnormalities (26,27). In humans, cases are known where translocations are associated with skeletal abnormalities and various other conditions.…”
Section: Extrapolation From Increased Mutation Rates To Adverse Healtmentioning
confidence: 99%
“…In addition, half of the gametes of a translocation carrier contain unbalanced, aneuploid segregants. Rutledge et al (27) found a high incidence of developmental anomalies in mice, as exencephaly and cleft palate among descendants of translocation carriers. Although the majority of these unbalanced zygotes will lead to stillbirths in man, 6% of these are assumed to result in congenitally malformed children (28).…”
Section: Extrapolation From Increased Mutation Rates To Adverse Healtmentioning
confidence: 99%